The Design and Simulation of a Quadruped Multi-mode Mobile Robot - Xinyue Yu; Chunyan Zhang; An Ping; Bing Ding; Jie Yang (Jixie chuandong)
In order to meet the needs of better completing tasks in a variety of terrains， a quadruped multi-mode mobile robot with walking mode， obstacle crossing mode and semi folding mode is designed， which can change the motion mode according to different terrains. When the robot is in walking mode， it can walk on ordinary flat road； when in obstacle crossing mode， you can climb over obstacles by raising the height of your legs； when in the semi folding mode， the wheelbase can be shortened through the folding of the platform for narrow road conditions. The freedom of the platform and leg of the mechanism is analyzed using the screw theory； the forward kinematic equation of the quadruped robot is solved by D-H parameter method； three modes of the robot are simulated by Adams simulation software. The results show that the robot can complete the tasks of walking， obstacle crossing and the half folding platform can pass through a certain width channel， which realize the multi motion mode of the robot.